2018
DOI: 10.1177/0040517517753635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fabrication methods for the effective loading of Ag onto PVA nanofibers

Abstract: We investigated and compared three different methods for synthesizing Ag/PVA nanofibers by effectively dispersing and loading Ag particles onto PVA nanofibers and preventing the detachment of Ag from the nanofibers. The three methods were: (a) the solution reduction method (Method 1) in which the reduction of Ag+ was conducted before electrospinning, resulting in mixing the polymer and the Ag nanoparticles in the electrospinning solution; (b) the immersion method (Method 2) in which electrospun PVA nanofibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 51 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…The higher proportion of HHK in the HHK/PEO/PVA ternary polymer system made the nanofibers more susceptible to the corrosion of acid and alkali than the nanofibers prepared in the literature [ 17 ]. These results indicated that the H + ions produced during the silver nitrate treatment and the excess alkali added to neutralize the H + ions had an etching effect on the fiber surface [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The higher proportion of HHK in the HHK/PEO/PVA ternary polymer system made the nanofibers more susceptible to the corrosion of acid and alkali than the nanofibers prepared in the literature [ 17 ]. These results indicated that the H + ions produced during the silver nitrate treatment and the excess alkali added to neutralize the H + ions had an etching effect on the fiber surface [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was analyzed that there were successful chemical interactions of functional groups between PVA and ZnO & TiO 2 NPs, as shown in Figure 5b–g. The spectra showed that in the neat PVA nanofibers, the bands at about 3320, 2940, 1437, 1093, and 850 cm −1 showed the vibrations of –OH, –CH 2 CH, C–C & C–O functional groups of PVA, respectively [18]. The new intense broad bands at 1100 cm −1 to 1000 cm −1 and 750 cm −1 are assigned to metal oxide of the of Zn & Ti, because these oxides have a moderate dipole moment.…”
Section: Resultsmentioning
confidence: 99%
“…2015, Augozi et al. 2014) and the characteristics peaks of C=O, C–CH 3 and C−O‐C of cellulose acetate at 1775, 1370 and 1100 cm −1 , respectively in all resultant …”
Section: Resultsmentioning
confidence: 90%